Online sexual exploitation of children applicable laws, casework perspectives, and recommendations - Aritao, Benjamin Lawrence Patrick E.; Pangilinan John Stephen B. (2018)
Children find themselves at the nexus of a worldwide human trafficking crisis in the form of extensive online sexual exploitation of children (OSEC). While the OSEC issue may not be broadly known, the United Nations Children's Fund has characterized the Philippines as "the global epicenter of the live stream sexual abuse trade." OSEC-related referrals to the Philippines have risen at alarming rates, now numbering in the thousands per month. A growing number of law enforcement OSEC operations involve domestic production of child exploitation materials. In these cases, suspects intentionally provide children online for the purpose of sexual exploitation, in return for profit -- the very definition of sex trafficking. As a virulent form of human trafficking, OSEC production must be addressed for what it is -- modern sex slavery perpetrated online. This article discusses the growing problem of OSEC in the Philippines. Its main idea is that effective law enforcement, robust prosecution, and nuanced victim care are essential in the fight to end OSEC.
Keywords: Sex trafficking of minors; Human trafficking; Children